N-Acetylcysteine may exert hepatoprotective effect by regulating Meteorin-Like levels in Adriamycin-induced liver injury - Kaya, Sercan; Yalcin, Tuba; Tektemur, Ahmet; Kuloglu, Tuncay (Elsevier Science Inc, 2023)
Adriamycin (ADR) is an important chemotherapeutic drug, but it has serious side effects such as hepatotoxicity. This study aimed to evaluate whether N-acetylcysteine (NAC) has hepatoprotective effects against ADR-induced hepatotoxicity in rats. In addition, it was aimed to determine how Meteorin-Like (MtrnL), which has pleiotropic effects on immunology, inflammation, and metabolism, is affected by ADR and/or NAC applications in liver tissue. 28 rats were randomly assigned to one of four equal groups in the study: control (no treatment), NAC (150 mg/kg/day of NAC intraperitoneally (i.p), ADR (15 mg/kg only on the first day of the experiment), and ADR + NAC (ADR 15 mg/kg on the first day of the experiment + 150 mg/kg/day NAC i.p). After 15 days, liver enzyme levels in serum, oxidant/antioxidant parameters in liver tissue, histopathological changes, caspase 3 (Casp3) and heat shock protein 70 (HSP-70) immunoreactivities, and MtrnL levels were examined. Histopathological changes, liver enzyme levels, as well as HSP-70, and Casp3 immunoreactivities increased due to ADR application. Additionally, MtrnL levels in liver tissue were significantly increased as a result of ADR application. However, it was detected that the NAC application significantly regulated the ADR-induced changes. Furthermore, it was determined that NAC administration regulated the changes in ADR-induced oxidative stress parameters. We propose that NAC may exert a hepatoprotective effect by regulating ADR-induced altered oxidative stress parameters, MtrnL levels, Casp3, and HSP-70 immunoreactivities in the liver.
Keywords: Adriamycin; N-Acetylcysteine; Meteorin-like; Heat shock protein 70; Caspase3; Hepatotoxicity